Is There an Incumbency Advantage or a Cost of Ruling in Proportional Election Systems? - Che-Yuan Liang (Uppsala University, Department of Economics, 2007)
This paper investigates the effect of political representation on the electoral outcome at the party level in a proportional multiparty election system using data from Swedish local government elections. There are two notions of representation in a council; the first is to hold seats, and the second is to belong to the ruling coalition. I refer to the effect of the former as the incumbency effect and the effect of the latter as the effect of ruling. To identify causal effects, I use the discontinuous variations in the number of seats and ruling (as a coalition receives a majority of the seats) to isolate exogenous variation in incumbency and ruling respectively. I find an advantage of 0.11 percent of the votes for each percent of incumbency. 11 percent of the votes in an election are therefore determined by incumbency, a figure close to the advantage found in majoritarian systems. However, the advantage differs significantly between parties. Further, I find no effects of ruling, contrary to the commonly found cost of ruling in proportional systems.
urn:nbn:se:uu:diva-12430
Keywords: D72; D73; 330; incumbency advantage; cost of ruling; proportional elections; multiparty systems; local governments; regression-discontinuity; Wahlsystem; Kommunale Selbstverwaltung; Schätzung; Wahlverhalten; Schweden